The Perbedaan Pengaruh Latihan Interval dan Latihan Fartlek terhadap Peningkatan Vo2max pada Atlet Lari Jarak Menengah Unimed Atletik Club (UAC) - Simanjuntak, Bernad (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aimed to determine the effect of interval and fartlek training on the VO2max value of middle distance runners at Unimed Athletic Club (UAC). This research is quantitative research where the research method used is the experimental method. The research sample consisted of 8 people and was divided into two groups, namely the interval training group and the fartlek training group, to determine the differences between the two types of training used. Apart from that, post analytical tests were carried out using normality, homogeneity, and hypothesis tests. Based on the research results obtained by the paired sample t-test, in the first hypothesis the significance value for the interval group is 0.020 < 0.05, so it can be concluded that there is a significant difference in VO2Max results before and after treatment in the interval group. The second hypothesis is that the significant value for the Fartlek group is <0.001; 0.05, so it can be concluded that there is a significant difference in VO2Max results before and after treatment in the Fartlek group. the fourth hypothesis, the significant value for the interval and fartlek groups is 0.037 <; 0.05, it can be concluded that fartlek training has a greater influence on increasing VO2max than interval training. Keyword: Fartlek, Interval, VO2Max